Imitation as a Valuable Elements of Ukrainian Social and Cultural Discourse - Krivoruchko, Natalia (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article devote consideration imitation how phenomenon, that processing Ukrainian transformation social, cultural, political process invariable one with main value landmark. Imitation, substitute, recurrence else’s form activity, behavior, making state, mentation place nowadays indispensability examination cause and essence imitation and suitably prediction consequences with this procedure in context Ukrainian making state. Basis on work up material and empirical observation offer main indications imitation in historical retrospective, thus in contemporary conditions challenges and transformations.